Economical efficiency of using a dispergator jet-slot type - Bratishko, V.; Kovalov, Oleksandr; Ковальов, Олександр Олександрович; Ковалев, Александр Александрович (My University, 2021)
Dispersion refers to the normative operations used in the milk processing, the fat content of which does not exceed more then 2–4%. Execution of this operation causes an increase in the unit cost of dairy products. This is explained by the fact that the energy costs of the process for the most common valve homogenization in the industry are more than 8 kWh/t of homogenized milk. Scientists have proposed 10 hypotheses that do not fully explain the theory of the process in the area of the valve slit, which is associated with high speeds of milk (over 100m/s) and microscopic particle size with an average diameter of 1 μm or less.
Keywords: dispergator jet-slot type; milk; energy costs